Assessment of anxiety, depression, social anxiety, anxiety sensitivity, and perceived stress in psoriasis patients: a controlled cross-sectional study - Taha Can Tuman; Betül Şereflican; Bengü Tuman (Journal of Contemporary Medicine, 2021)
Objective: Psoriasis is a chronic inflammatory skin disease, and psychiatric comorbidities are common in these patients. Skin lesions can cause shame, anxiety, social avoidance, irritability, and depressive symptoms in psoriasis patients. This study aimed to investigate anxiety, depression, social anxiety, anxiety sensitivity, and perceived stress in patients with psoriasis and their relationship with disease severity and duration. Methods: Forty patients and 40 healthy controls were included in our study. All study patients were administered the Beck Anxiety Inventory (BAI), the Beck Depression Inventory (BDI), the Liebowitz Social Anxiety Scale (LSAS), the Perceived Stress Scale (PSS-14), and the Anxiety Sensitivity Index (ASI-3). Disease severity in psoriasis patients was assessed using the Psoriasis Area Severity Index (PASI). Results: Anxiety, depression, social anxiety, perceived stress, and anxiety sensitivity were significantly higher in psoriasis patients than in healthy controls. There was no correlation between PASI scores and BAI, BDI, LSAS, PASS-14 and ASI-3 scores. Also, no correlation was found between disease duration and BAI, BDI, LSAS, PSS-14 and ASI-3 scores. Conclusion: Our results show that anxiety, depression, social anxiety, anxiety sensitivity, and perceived stress are high in psoriasis patients regardless of disease duration and severity. This is the first study to examine anxiety sensitivity in psoriasis patients to the best of our knowledge. Clinicians should consider the possible psychiatric comorbidity at all stages of the disease in patients with psoriasis. Collaboration between the disciplines of dermatology and psychiatry is necessary to ensure full recovery and maintain patient well-being.